Proteasome inhibitors prevent bi-directional HER2/estrogen-receptor cross-talk leading to cell death in endocrine and lapatinib-resistant HER2+/ER+ breast cancer cells - Thaler, Sonja; Roßwag, Sven; Sleeman, Jonathan P. (OncoTarget, 2017)
Amplification and/or overexpression of the human epidermal growth factor 2 (HER2) oncogene occurs in about 13–15% of invasive breast cancer and triggers breast cancer cell proliferation, survival and metastatic progression. Around half of all breast cancers with HER2 overexpression co-express hormone receptors (HR) such as those for estrogen and progesterone. Aberrant signaling through HER2 and other members of the HER-family mediates endocrine-resistance in estrogen receptor alpha (ERα) positive breast cancer. On the other hand, ERα co-expression has been shown to attenuate the efficiency of anti-HER2 therapies. These findings indicate that HER2 and ERα synergize to escape from both anti-ERα and anti-HER2-targeted therapies. Rationally designed clinical trials that combine endocrine therapy with anti-HER2 agents to interfere with HER2/ERα cross-talk have been conducted. However, the outcome of these trials suggests that novel therapeutic approaches are needed to further improve inhibition of HER2 and other HER-family members in conjunction with a more efficient ERα blockade. Here, we demonstrate that carfilzomib and bortezomib stabilize the HER2-specific protein tyrosine phosphatase BDP1 leading to decreased HER2 autophosphorylation, reduced HER2 activity and subsequently attenuated activation of the PI3K/Akt-pathway, together with blockade of ERα expression. We further observed that proteasome inhibitors (PIs) reverse autophosphorylation and thereby inhibit the activity of constitutively active mutant HER2. We also demonstrate that PIs cause cell death in lapatinib and endocrine-resistant HER2+/ER+ breast cancer cells. These findings suggest that PIs might have the potential to improve the management of HER2+/ER+ breast cancer patients by efficiently disrupting the bi-directional HER2/ERα cross-talk.